Inorganic Ammonium Halide Additive Strategy for Highly Efficient and Stable CsPbI3 Perovskite Solar Cells. (19th March 2021) - Tan, Shan; Shi, Jiangjian; Yu, Bingcheng; Zhao, Wenyan; Li, Yusheng; Li, Yiming; Wu, Huijue; Luo, Yanhong; Li, Dongmei; Meng, Qingbo
Abstract: All‐inorganic perovskite cesium lead iodide (CsPbI3 ) exhibits excellent prospects for commercial application as a light absorber in single‐junction or tandem solar cells due to its outstanding thermal stability and proper bandgap. However, the device performance of CsPbI3 ‐based perovskite solar cells (PSCs) is still restricted by the unsatisfactory crystal quality and severe non‐radiative recombination. Herein, inorganic additive ammonium halides are introduced into the precursor solution to regulate the nucleation and crystallization of the CsPbI3 film by exploiting the atomic interaction between the ammonium group and the Pb–I framework. The grain boundaries and interfacial contact of the CsPbI3 film have been improved, which leads to significant suppression in the non‐radiative recombination and an enhancement in the charge transport ability. With these benefits, a high efficiency of 18.7% together with an extraordinarily high fill factor of 0.83–0.84 has been achieved, comparable to the highest records reported so far. Moreover, the cell exhibits ultra‐high photoelectrical stability under continuous light illumination and high bias voltage with 96% of its initial power‐conversion efficiency being sustained after 2000 h operation, even superior to the world‐champion CsPbI3 solar cell. The findings are promising for the development and application of all‐inorganic PSCs using a simple inorganic additive strategy. Abstract : Highly efficient and stable γ‐CsPbI3 perovskite solar cells (PSCs) can be obtained using a simple inorganic additive strategy by regulating the nucleation and crystallization process of the CsPbI3 film. Improved grain boundaries and interfacial contact of the CsPbI3 film lead to significant suppression in the non‐radiative recombination, which shows better efficiency and remarkable stability in all‐inorganic PSCs.